2021
DOI: 10.1111/1759-7714.13818
|View full text |Cite
|
Sign up to set email alerts
|

ALK‐rearranged squamous cell carcinoma of the lung

Abstract: Background ALK rearrangement is a very rare subset of squamous cell carcinoma (SCC) and one of the clinical features in patients is lack of data. Here, we report eight patients diagnosed with SCC of the lung harboring ALK rearrangement. Methods We collected primary NSCLC samples at the Beijing Chest Hospital between January 2012 and December 2018 for Ventana (D5F3) immunohistochemical detection. Among the 148 patients was diagnosed ALK‐rearranged non small cell lung cancer (NSCLC), only eight cases was SCC. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…ALK LUSC outcome is especially inferior compared with ALK LUAD, consistent with multiple previous studies that reported LUSC harboring an EML4-ALK rearrangement were unsuccessfully treated with ALK TKI. 15 The therapeutic effect of ALK TKI in patients with LUSC remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…ALK LUSC outcome is especially inferior compared with ALK LUAD, consistent with multiple previous studies that reported LUSC harboring an EML4-ALK rearrangement were unsuccessfully treated with ALK TKI. 15 The therapeutic effect of ALK TKI in patients with LUSC remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…presented a single-center case review of 31 ALK-positive LSCC patients, of whom 20 received ALK-TKIs as their initial or subsequent treatment. The median PFS in this group was 6.4 months ( ± 4.4 months), notably shorter than that observed in ALK-positive LADC patients treated with ALK inhibitors ( 10 ). Lu et al.…”
Section: Discussionmentioning
confidence: 52%
“…Clinically, the ALK rearranged SQCC patients also obtained benefit from ALK -TKIs, but was not as beneficial as compared to the ADC patients ( 21 , 22 ). In this case, different therapeutic effects of ALK -TKI treatment were observed in two different morphological sites.…”
Section: Discussionmentioning
confidence: 88%